A Miniature Radial-Flow Wind Turbine Using Piezoelectric Transducers and Magnetic Excitation. (November 2015) - Fu, H; Yeatman, E M
Abstract: This paper presents a miniature radial-flow piezoelectric wind turbine for harvesting airflow energy. The turbine's transduction is achieved by magnetic "plucking"of a piezoelectric beam by the passing rotor. The magnetic coupling is formed by two magnets on the beam's free end and on the rotor plate. Frequency up-conversion is realized by the magnetic excitation, allowing the rotor to rotate at any low frequency while the beam can vibrate at its resonant frequency after each plucking. The operating range of the device is, therefore, expanded by this mechanism. Two arrangements of magnetic orientation have been investigated, showing that the repulsive arrangement has higher output power. The influence of the vertical gap between magnets was also examined, providing guidance for the final design. A prototype was built and tested in a wind tunnel. A peak power output of 159 μW was obtained with a 270 kΩ load at 2.7 m/s airflow speed. The device started working at 3.5 m/s and kept operating when the airflow speed fell to 1.84 m/s.